Improving Network Performance of IP PBX Based Telecommunication System - Wardi, Wardi; Basri Hasanuddin, Zulfajri; Andani, Andani; Jo Salli, Jeffry; Muhammad Syafaat, Andi (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol 11 No 2 (2020): Vol. 11, No. 2 August 2020DO - 10.24843/LKJITI.2020.v11.i02.p04, 2020)
IP-PBX based communication has become a human need in the era of technology. Some researchers design a wireless telecommunication system based on IP PBX using Raspberry Pi. The previous researches have small network coverage and problematic on the ability of the system to support multiple concurrent connections. Based on these problems, these research aims are to expand the coverage area and increase the number of concurrent calls. This study used Asterisk FreePBX for the media configuration of the servers. The clients: laptops and smartphone devices used Linkin and Bria softphone. The testing was conducted in terms of voice and video services in the form of signal strength, CPU performance of servers, and network performance parameters such as delay, jitter, and packet loss. The results obtained that the CPU performance of the servers for seven calls simultaneously is around 16.9% compared with previous research, at an average of 45%. Based on ETSI standards, the measurement of network performance parameters when communicating between clients outperform than previous research. The clients can communicate well up to 390 meters.